Annual Sedimentary Record From Lake Donguz-Orun (Central Caucasus) Constrained by High Resolution SR-XRF Analysis and Its Potential for Climate Reconstructions - Alexandrin, Mikhail Y.; Darin, Andrey V.; Kalugin, Ivan A.; Dolgova, Ekaterina A.; Grachev, Alexi M.; Solomina, Olga N. (Frontiers in Earth Science, 2018)
Bottom sediments of the proglacial Lake Donguz-Orun situated at 2500 m a.s.l. in the Elbrus Region (Central Caucasus) reveal regular laminae, characteristic of proglacial varved lakes. This is the first laminated sediment sequence recorded in the region. However, visual counting of the layers was restricted due to partial indistinctness of the lamination. In order to confirm the annual sedimentary cyclicity and proceed with annually resolved data, in addition to the visual identification we used high resolution geochemical markers. The upper 160 mm of the sediment core were scanned at 200 µm intervals using synchrotron radiation X-ray fluorescence analysis (SR-XRF). Additional ultrahigh resolution scanning at 30 µm increments was employed for the upper 20 mm of the core. The Rb/Sr and Zr/Rb ratios are interpreted to record annual changes in grain-size. Based on this geochemical assessment, we identified 88 annual layers covering the interval between 1922 and 2010, while visually we have been able to identify between 70 and 100 layers. The correctness of the geochemical results is confirmed by mean accumulation rates assessed by 137Cs and 210Pb dating. Cross-correlation between the ring width of local pine chronology and the layer thickness, identified as a distance between the annual Rb/Sr peaks, allowed for the accurate dating of the uppermost preserved year of the sediment sequence (AD 2010). Annually averaged elemental data were then compared with regional meteorological observations, glacier mass balance and tree-ring chronologies. The comparison revealed notable conformities: content of bromine is positively correlated with annual temperatures (r=0.41, p<0.01), content of terrigenous elements (major elements with the origin in watershed rocks) is positively correlated (up to r=0.44, p<0.01) with annual precipitation. A high statistically significant negative relationship is observed between the concentrations of terrigenous elements and tree-ring width of local pine chronology (up to r=-0.56, p<0.01). Taken together, these data point to a common composite climatic signal in the two independent records (lake sediments and tree rings) and confirm that the laminae represent annual layers (i.e., varves). These findings open opportunities for high resolution multiproxy climate reconstructions 300-350 years long using the longer sediment core and tree-ring records.